Fountains and water features : from ancient springs to modern marvels - Hopwood, Rosalind (London : Frances Lincoln, 2009)
A key design element since the first gardens were tilled, water has been managed into a surprising range of styles $1 (Bin symbolic and mythological themes, for private contemplation, and for large-scale displays of power and wealth. This book traces the history of fountains and describes key examples such as Moorish water gardens in Spain, Renaissance pleasure fountains, impressive schemes at Chatsworth and Vaux le Vicomte, and a wide range of contemporary cascades. More than 150 color illustrations depict these inspiring features.s
Keywords: Fountains; Water in landscape architecture